2013
DOI: 10.1007/s11239-013-1028-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of circulating blood and endothelial cell microparticles in sickle-cell disease

Abstract: Increased thrombocyte activation leads to a higher likelihood of coagulation in sickle-cell disease. On the other hand, chronic inflammation and endothelial cell activation promote vaso-occlusion. The effect of circulating microparticles derived from erythrocytes, monocytes, thrombocytes, and endothelial cells on the vaso-occlusive process is unclear. This study aims to analyze the relationship between sickle-cell disease and miscellaneous organ complications by defining the circulating microparticles during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 19 publications
8
41
2
Order By: Relevance
“…There are conflicting reports on the association of platelet activation with TRV, with one study showing a correlation between activated GPIIb/IIIa receptor with TRV (73), while another showed no association between soluble CD40 ligand and TRV (40). Furthermore, higher levels of both platelet- and erythrocyte-derived microparticles have been reported in patients with histories of ACS and elevated TRV compared to those without either of these complications (143), although no significant differences were seen in the plasma concentrations of total-, endothelial cell derived-, and TF-positive microparticles in another study (91). …”
Section: Thrombosis-related Complications Of Scd and The Link Withmentioning
confidence: 86%
See 3 more Smart Citations
“…There are conflicting reports on the association of platelet activation with TRV, with one study showing a correlation between activated GPIIb/IIIa receptor with TRV (73), while another showed no association between soluble CD40 ligand and TRV (40). Furthermore, higher levels of both platelet- and erythrocyte-derived microparticles have been reported in patients with histories of ACS and elevated TRV compared to those without either of these complications (143), although no significant differences were seen in the plasma concentrations of total-, endothelial cell derived-, and TF-positive microparticles in another study (91). …”
Section: Thrombosis-related Complications Of Scd and The Link Withmentioning
confidence: 86%
“…“Steady state” plasma levels of markers of in vivo thrombin and fibrin generation were not associated with histories of leg ulcers, retinopathy or priapism in adult SCD patients (24), nor with histories of splenic sequestration, hemolytic or aplastic crises in children (23). The number of platelet-derived microparticles was reported to be significantly higher in adult patients with albuminuria compared to those without, but no differences were observed in total microparticles or other circulating cell-derived microparticles (91). …”
Section: Thrombosis-related Complications Of Scd and The Link Withmentioning
confidence: 97%
See 2 more Smart Citations
“…In children, both platelet and erythrocyte microparticle levels were positively correlated with aortic stiffness and pulmonary artery pressure, while they were found to correlate negatively with aortic distensibility 25. Nébor et al reported hydroxyurea treatment to be associated with a decrease in microparticles derived from erythrocytes and platelets,26 whereas in another study endothelial microparticle levels were not affected by hydroxyurea treatment 22…”
Section: Extracellular Vesicles In Hemoglobinopathiesmentioning
confidence: 98%